Investigation of the compaction behaviour of a quasi-unidirectional non-crimp fabric during the vacuum infusion process. (July 2022) - Droste, David; Krishnappa, Likith; Bornemann, Sarah; Ohlendorf, Jan-Hendrik; Vargas Gleason, Minerva G; Herrmann, Axel S; Lang, Walter
The compaction behaviour of technical textiles such as non-crimp fabrics (NCF) is of much interest to build high quality parts in liquid composite moulding processes (LCM). In this paper, the compaction response of a glass fibre NCF was investigated in two different ways: (1) characterisation tests via a universal testing machine and (2) height measurements via a line laser measurement unit during the infusion process. Results from both measurement systems are compared and it is found that the results of characterisation tests via testing machine can be used only to a certain extent. The pressure-thickness correlation during the infusion process cannot be described by the results of the testing machine, while the compaction results before and after the infusion process are in good agreement for both the methods. With the data of the line laser measurement, a model for the pressure-thickness correlation is derived, which can be used in future simulations. The infusion process was carried out using different scenarios at the vent, on the one hand a semi-permeable membrane and on the other hand an omega profile at the venting port. The results obtained using these two different venting scenarios were compared and it was found that using a semi-permeable membrane as an outlet can lead to thicker parts (up to 10 % ).